DYNAMICS OF CLINICAL LABORATORY PARAMETER IN HIV-INFECTED CHILDREN UNDERGOING DIFFERENT PATTERNS OF INITIAL HIGHLY ACTIVE ANTIRETROVIRAL THERAPY: RANDOMIZED CONTROLLED TRIAL - V. B. Denisenko; E. N. Simovanyan (Union of pediatricians of Russia, 2016)
Background: Adverse course of HIV infection, rapid development of immunosuppression, severe opportunistic infections and malignant tumors and high mortality substantiate the importance of timely prescription of highly active antiretroviral therapy (HAART). The initial therapy pattern must remain efficient and safe in the long term.Objective: Our aim was to study effectiveness and safety of different patterns of initial HAART in HIV-infected children.Methods: The randomized controlled trial involved HIV-infected children aged 1-3 years. Clinical, immunological and virological examinations were conducted before and 12 months after HAART. The initial therapy pattern included 2 nucleoside HIV reverse transcriptase inhibitors - zidovudine and lamivudine. Children were randomized to the groups differing in the third therapy component: lopinavir/ritonavir or nevirapine.Results: 25 patients were randomized to the lopinavir/ritonavir group, 23 children - to the nevirapine group. After 12 months of treatment, HIV replication suppression (blood viral load < 50 copies/ml) was achieved in 25 (100%) lopinavir/ritonavir group patients and in 16 (70%) nevirapine group patients (p = 0.003). HIV infection did not progress clinically regardless of the pattern. The median number of CD4+CD3+ lymphocytes in the lopinavir/ritonavir group increased from 20.5% (12; 23) to 30% (27; 34) (p < 0,001), in the nevirapine group - from 21.5% (17; 23) to 29% (27; 38) (p < 0.001). Adverse events developed in 13 (27%) children. 3 and 2 children in the lopinavir/ritonavir group suffered from nausea and emesis, respectively. 1 and 1 patient in the nevirapine group suffered from allergic rash and drug-induced hepatitis, respectively.Conclusion: High effectiveness and safety of lopinavir/ritonavir allow recommending this drug as the third component of the initial HAART pattern for HIV-infected children.